Control interno y su incidencia en la gestión administrativa de la cooperativa de taxis san camilo, cantón quevedo, año 2023 - Zamora Aguilar, Milena Karelys (2025)
The present research, titled "INTERNAL CONTROL AND ITS IMPACT ON THE ADMINISTRATIVE MANAGEMENT OF THE SAN CAMILO TAXI COOPERATIVE, QUEVEDO CANTON, YEAR 2023," focuses on understanding the internal control mechanisms applied in the organization's administrative area. The main objective is to evaluate the impact of internal control on the administrative management of the San Camilo Taxi Cooperative during the year 2023. The methodology used includes field, descriptive, and explanatory research, applying inductive, deductive, and analytical methods. The population and sample consisted of eight members from the administrative area. Observation and interview techniques were applied, using tools such as observation guides, internal control questionnaires based on the COSO III model, interview formats, and documented records. The results were obtained through interviews with administrative members to analyze the policies and procedures in place. The efficiency level of the operational processes was determined using performance indicators. The Internal Control evaluation, based on the COSO III model, made it possible to identify and assess the risks present in administrative management. Based on the findings, a report was issued, and a proposal matrix was developed to strengthen both internal control and the administrative management of the cooperative.